The impact of gender on tumour stage in in-house complications and choice of urinary diversion: results of the Austrian cystectomy registry - Gschliesser, Tanja; Pelzer, Alexandre E. (Urologia internationalis, 2017)
Introduction and Objectives: Bladder cancer is characterized by gender-dependent disparities. To further address this issue, we analysed a prospective, multicentre cystectomy registry. Methods: An online database was developed that included patient demographics, intra/perioperative data, surgical data and in-house complications. Results: Four hundred fifty-eight patients (112 [24.5%] women and 346 [75.5%] men) were analysed. Men and women were comparable regarding age (mean 68 years), body mass index (mean 26.5) and the mean Charlson score (4.8). Women had more advanced tumour-stages (pT3/pT4; women: 57.1%; men: 48.1%). The rate of incontinent urinary diversion was higher in women (83.1%) than in men (60.2%) and in a multivariate analysis, the strongest predictors were M+ status (OR 11.2), female gender (OR 6.9) and age (OR 6.5). Women had a higher intraoperative blood transfusion rate. The overall rate of in-house complications was similar in both genders (men: 32.0%, women: 32.6%). Severe (Clavien-Dindo grade >2) medical (women: 6.3%; men: 5.2%) and surgical (women: 21.5%; men: 14.4%) in-house complications, however, were more frequent in women. Conclusions: This multicentre registry demonstrates several gender-related differences in patients undergoing radical cystectomy. The higher transfusion rate, the rare use of orthotopic bladder substitutes and the higher in-house complication rate underline the higher complexity of this procedure in women.